An SLS5 Longitude System Based on the Rotational Modulation of Saturn Radio Emissions. Issue 15 (8th August 2018) - Ye, S.‐Y.; Fischer, G.; Kurth, W. S.; Menietti, J. D.; Gurnett, D. A.
Abstract: Despite the axisymmetry of Saturn's internal field, Saturn radio emissions like Saturn kilometric radiation (SKR) are modulated due to planetary rotation. With the completion of Cassini mission in September 2017, we now have around 14 years of observation of Saturn radio emissions, roughly from southern solstice to northern solstice. In this study, we extend the SLS4 longitude system to the end of the Cassini mission using a phase tracing method. The new Saturn longitude system (SLS5) organizes the observed SKR maxima around 0° subsolar longitude in both northern and southern hemispheres and can be used to organize other phenomena observed in Saturn's magnetosphere, for example, hot plasma injection events. SKR is modulated like a clock when the main source on the morning side is visible. To convert the observed phase to the clock phase, the phase of the morning side source, we also define a second longitude system SLS5*, which takes the spacecraft position into account based on a simple visibility model. Plain Language Summary: A new Saturn longitude system is defined based on the modulation phase of Saturn radio emissions, which can be used to organize other magnetospheric phenomena observed by Cassini at Saturn. Key Points: Saturn's radio emissions are modulated at periods close to the planet's rotation period The modulation periods display hemispherical asymmetry and seasonal variation A new longitude system is defined based on the modulation phase of SKR